Pengaruh Book Value per Share (BVS) pada Lembaga Keuangan Syariah dan Konvensional: Studi Bibliometrik VOSviewer dan Literature Review - Budianto, Eka Wahyu Hestya; Dewi, Nindi Dwi Tetria (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This study aims to determine the effect of Book Value per Share (BVS) on Islamic and Conventional Financial Institutions with a mix-method approach, namely quantitative methods in bibliometric studies and qualitative methods in literature review studies. The object of research is the risk of financing. Sources of data collection come from searches of national and international journals indexed by Google Scholar, Sinta, and Scopus through the Perish/Harzing application. Data analysis techniques include: (1) mapping the effect of BVS using a bibliometric study with the VOSviewer algorithm software; and (2) mapping the effect of BVS using a literature review study. The results showed that based on the VOSviewer bibliometric study, research on the influence of BVS was divided into 4 clusters and 74 topic items. Meanwhile, based on a literature review study, there are 4 influences of BVS on Islamic and Conventional Financial Institutions. The implication and contribution of this research is to map topics that are often researched by researchers, so that they can be a reference for subsequent researchers.